Particle Swarm Optimization Technique for Optimizing Conditional Value-at-Risk Based Portfolio - Ray, J; Bhattacharyya, S (International Journal of Computer Sciences and Engineering, 2025)
In existence of instability within the financial dealings, a reasonable harmony among risks and returns has to be managed by an investor to derive at an optimum standpoint. Although there is a predominant instability, the advantage lies in the correlation of the combination of financial instruments/assets in a financial portfolio within a specific market condition. Portfolio management targets the risk-reward accord in allocation of investments directed towards numerous assets for maximizing returns or minimizing risks within a stipulated investment period. This article delineates the particle swarm optimization algorithm, followed by optimized portfolio asset distribution within a changeable market condition. The suggested way is consolidated for optimization of the Conditional Value-at-Risk (CVaR) measurement within divergent market conditions established on numerous targets and restraints. Results are compared to the values obtained by the optimization of Value-at-Risk (VaR) measurement of the portfolios under consideration.